THE ROLE OF MANAGEMENT IN THE GERMAN ECONOMY - Gafforova , Visola (Science technology&Digital finance, 2023)
This article provides feedback on the problems that arise in the management system in Germany and their solutions. The results achieved by Germany in the field of exports and imports will also be touched upon.